miR-375 Is Down-Regulated in Squamous Cervical Cancer and Inhibits Cell Migration and Invasion via Targeting Transcription Factor SP1 - Wang, Fenfen (American Society for Investigative Pathology, 2011)
Pelvic lymph node metastases are regarded as the most important risk factor and a predictor of poor prognosis for patients with cervical cancer. Exploration of metastasis-related molecules is helpful toward improving the prognosis in cervical cancer. To identify the role of miR-375 in metastasis and progression of cervical cancer, we examined the expression of miR-375 in 170 cervical cancer tissues and 68 normal cervical tissues, using stem-loop quantitative PCR, and found that the expression of miR-375 in cervical cancer tissues was significantly decreased by 4.45-fold, compared with 68 normal tissues. A significant correlation existed between miR-375 expression and clinicopathologic parameters, including lymph node metastasis of cervical cancer. Overexpressed miR-375 suppressed cell proliferation, blocked G1-to-S cell-cycle transition, and inhibited cell migration and invasion in human cervical SiHa and CaSki cells. SP1, a potential target gene of miR-375, was inversely correlated with miR-375 expression in cervical cancer tissues. Moreover, SP1 was negatively regulated by miR-375, and knockdown of SP1 by siRNA inhibited cell malignant behaviors. Thus, our findings suggest that down-regulated miR-375 promotes cell malignant behaviors via the target gene SP1 and may consequently contribute to the progression of cervical cancer.